THE EFFECTIVENESS OF SHADOWING TECHNIQUE IN ENHANCING PRONUNCIATION SKILL OF EIGTH GRADE STUDENT AT SMP NEGERI 8 GORONTALO - Alief Bahasoan; Hanisah Hanafi; Irmawaty Umar (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
This study investigates the effectiveness of the shadowing technique in improving word-stress pronunciation of eighth-grade students at SMP Negeri 8 Gorontalo. Using a one-group pretest–posttest quantitative design, thirty-two students (class VIII-2) participated in six scaffolded shadowing sessions. Pronunciation performance on a 10-item word list was recorded and scored using the Speakometer application; pretest and posttest scores were subsequently analyzed with a paired-samples t-test. Results indicate a substantial improvement in mean scores from 37.65 (SD = 11.29) at pretest to 70.03 (SD = 11.90) at posttest, and the difference was statistically significant (paired t, p = .000), supporting the alternative hypothesis that shadowing significantly enhances word-stress accuracy. Classroom observations suggested that gains stemmed from improved stress placement, clearer vowel reduction in unstressed syllables, and greater prosodic automaticity following graded practice and peer/teacher feedback. While limitations include the single-group design, single-class sample, and short intervention window, findings suggest that teacher-guided shadowing combined with app-based feedback is a practical and effective method for addressing word-stress issues in EFL middle-school contexts. Implications for pedagogy and directions for controlled, larger-scale studies are discussed.